Synthesis and characterization of a new polyaminocarboxylic macrocyclic ligand and its non-ion gadolinium complex. In vitro relaxivity studies at 0.2 T - Martinez, Mario David (2015)
In this study a novel ligand with three carboxylic groups (H3L1 ) was synthesized. Its non-ion complex with GdL1 holding promise of magnetic resonance imaging (MRI) was synthesized, and the relaxivity of the complex determined. The relaxivity of GdL1 (R1 = 4.5 Mmol−1 ·s−1 ) was larger than that of Gd(DTPA)2−(R1 = 3.9 Mmol−1 ·s−1 ). The results showed that the non-ion complex is a prospective MRI contrast agent.